Digitisation of the WA Welcome Wall collection: a case study - Joseph, Pauline; Gregg, M.; May, S. (Australian Society of Archivists Inc, 2013)
This article is focused on the partnership between the WA Museum Maritime History Department and Curtin University’s Information Studies Department on a retrospective digitisation project in 2012. The aim was to digitise the Welcome Wall project’s paper records and link these records to the museum’s online maritime history collection. The paper outlines and discusses the key business process questions that were considered prior and during the embarkation on the digitisation project. The conclusion shares lessons learnt from the project.